Comparative analysis of legal mechanisms to net-zero: lessons from Germany, the United States, Brazil, and China - L. Delta Merner; Lisa Benjamin; William Ercole; Isabela Keuschnigg; Julian Kunik; Karla Martínez Toral; Laura Peterson; Joana Setzer; Karen Sokol; Aradhna Tandon; Kaia Turowski (Carbon Management)
Amid mushrooming net-zero commitments and pledges made by states and non-state entities, a gap remains between those pledges, and the action needed in order to stay within the temperature goals of the Paris Agreement. In response, scholars and policymakers have started to examine physical, technological, economic, and policy pathways to net‐zero emissions across different sectors. This article examines the existing legislation and litigation for a net-zero world in four jurisdictions: Germany, the United States, Brazil, and China. We propose a taxonomy for identifying and comparing existing legal mechanisms to reach net-zero across these jurisdictions. We identify and analyze different legislative and regulatory mechanisms that incorporate net-zero mandates and three net-zero litigation strategies in these countries. These jurisdictions provide a useful snapshot of the variety of legal mechanisms currently being used by, or imposed on, large emitting jurisdictions and entities. We then consider the critical ways in which climate law can contribute to, or hinder, emissions reductions in line with net-zero targets.